Framing Assad’s Fall on British Broadcasting Corporation Arabic and Alhadath: An Entman Analysis - Nadia Sailil Fadhilah; Abdul Muntaqim Al Anshory (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
International media coverage of the collapse of Bashar al-Assad's regime varies in its presentation, which has the potential to shape different public perceptions. How did BBC News Arabic and Al-Hadath present the collapse of this regime in a relatively short period of time? This study analyzes the differences in presentation using Robert Entman's model, which includes problem definition, diagnosis of causes, moral assessment, and recommended solutions. The primary data consists of two YouTube videos: “The Fall of Bashar al-Assad's Regime in 12 Days” from BBC News Arabic and “The Story of the Fall of the Assad Regime in 10 Days” from Al-Hadath, supplemented by secondary sources. The qualitative methods used include listening, reading, and note-taking techniques, with a three-stage analysis according to Miles and Huberman. The results show that BBC News Arabic emphasizes the military operations of opposition forces that seized strategic areas (Aleppo, Hama, Damascus), the weakening of the regime's control, and human rights violations. Al-Hadath highlights the political transition through the official declaration of the former Syrian prime minister, which marks a new political era. Both media outlets show different framing strategies in presenting the narrative of Assad's downfall.